A Nutraceutical Formula Is Effective in Raising the Circulating Vitamin and Mineral Levels in Healthy Subjects: A Randomized Trial - Nenseth, Hatice Zeynep; Sahu, Aparna; Saatcioglu, Fahri; Osguthorpe, Steven (Frontiers in Nutrition, 2021)
Low levels of nutrient intake is common in industrialized countries, have negative implications for health, and is associated with chronic disease. Supplementation of vitamins, minerals and key nutrients to optimal levels may therefore be beneficial for individual health, as well as for the health economy. Although use of supplements have become very common, due to lack of monitoring, there is very limited data on the efficacy of supplementation with different formulas. Here we present results of a randomized controlled study on the efficacy of a novel formulated nutraceutical, N247, in 250 healthy volunteers aged 26-75 years as well as a placebo control group (n=35). N247 includes a broad spectrum of essential vitamins, minerals, and trace elements to take best advantage of the combined synergies and related metabolic functions of these nutrients, including high degree of nutrient bioavailability, tolerance, and safety with daily, long-term use. After three months of regular N247 use, levels of vitamins and minerals in serum were significantly increased in the N247 group compared to the control group, as well as a placebo group, with excellent compliance rates. Coupled to additional natural ingredients that aim to increase the potency of the nutrients, N247 may represent a novel and beneficial supplement for individuals with nutritional deficiencies. Clinical Trial Registration: https://clinicaltrials.gov/ (identifier: NCT04054505).